Melawan Gelap di Usia Muda Terhadap Analisis Faktor Penyebab dan Solusi Pencegahan Kenakalan Remaja Akibat Narkoba dan Miras - Rezki, Moch. Gufron Fajar; Rudiyansah, Muhammad Mas Davit Herman (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Adolescent addiction related to drug and alcohol (miras) abuse is a complex and multidimensional social problem. This phenomenon is closely linked to a crisis in the family institution, peer pressure, weakened educational supervision, and the ease of access to addictive substances. Adolescence, as a phase of identity exploration, makes individuals particularly vulnerable to external influences—especially when the social environment fails to provide positive support. The abuse of drugs and marijuana by adolescents is often a form of escape from psychological stress, identity confusion, or negative peer influence. A sociological approach is essential to holistically understand the root causes of this issue by identifying the structural and cultural factors that shape deviant behavior among adolescents. This study aims to explore the causes of adolescent delinquency stemming from drug and alcohol abuse and to formulate prevention strategies that are educational, persuasive, and participatory. Effective prevention requires the involvement of four main pillars: family, school, community, and the state. The family acts as the first line of defense in shaping adolescent character; schools serve as centers of moral development; communities provide a supportive social environment; and the state functions as a policy-maker and enforcer in protecting the younger generation. Legal measures alone are insufficient—preventive efforts must also include value-based approaches, education, and rehabilitation. Through cross-sectoral collaboration and collective awareness, the negative impacts of drug and alcohol abuse among adolescents can be minimized, enabling them to grow into healthy, resilient, and morally grounded individuals who contribute positively to the nation’s future.